PENGETAHUAN PASANGAN USIA SUBUR TENTANG PROGRAM KB DI RW 08 KELURAHAN TANGKERANG TENGAH PEKANBARU - Fernando, Tomi; Natuna, Daeng Ayub; Irja, Desti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the knowledge pair age fertile about family planning in the RW 08 Kelurahan Tangkerang Tengah Pekanbaru city. The problem was how high the knowledge of ferltile couple about family planning program in the RW 08 Kelurahan Tangkerang Tengah Pekanbaru city? .This is a descriptive study with a quantitative approach which aims to describe the result with figures. The sampling technique using a quota sampling technique, which is a technique for determining a sample of the population that have certain characteristics until the expectations of the amount of quota. Data collection techniques in this study is by using a test, which was 46 objective question that was distributed to 72 mothers fertile age in the RW 08 Kelurahan Tangkerang Tengah. The result show that knowledge of fertile couple about family planning program in the indicator purpose and knowledge on family planning is highest with the value of mean 0,675 and Standard Deviation (SD) 0,533 compared 2 others indicators. It’s mean Fertile couple more knowing about the purpose and knowledge on family planning generally but not for detailed.Keywords: Knowledge, Pair Age Fertile couple, Family Planning Program